2017
DOI: 10.1021/acs.jproteome.7b00247
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Analysis of SOX11-Binding Proteins in Head and Neck Cancer Cells Demonstrates the Interaction of SOX11 and HSP90α

Abstract: Deregulated expression of SOX11 has been shown to be involved in the progression of various types of cancer. However, the role of SOX11 in head and neck cancer remains largely unknown. In this study, coimmunoprecipitation (Co-IP) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were performed to identify the proteins that bind to SOX11 at significantly higher levels in head and neck cancer cells than in normal human oral keratinocytes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The prognostic protein UBR4, not included by STRING, is also associated with EGFR (18) and was manually added to the network. Similarly SOX11, reported to interact with GART (19), was manually added to the network (Figure 6). Thus, after manual curation, of the 9 discovered proteins with potential prognostic utility in TNBC, all except the two proteins without known functions (CCDC24 and ZSWIM8) could be functionally linked in a network centered on EGFR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic protein UBR4, not included by STRING, is also associated with EGFR (18) and was manually added to the network. Similarly SOX11, reported to interact with GART (19), was manually added to the network (Figure 6). Thus, after manual curation, of the 9 discovered proteins with potential prognostic utility in TNBC, all except the two proteins without known functions (CCDC24 and ZSWIM8) could be functionally linked in a network centered on EGFR.…”
Section: Resultsmentioning
confidence: 99%
“…SOX11, described by others as a marker of poor prognosis in basal-like breast cancer (48)—although another study unstratified for subtype did not show this effect (49)—has been proposed as a therapeutic target in breast (48) and other (50) cancers. As noted above, SOX11 can be included in the STRING network through its interaction, identified by coimmunoprecipitation and LC-MS/MS (19) with the purine biosynthetic protein GART. Thus, of the 9 proteins we have identified by MALDI MSI as having potential prognostic value in TNBC, only the two without known function (CCDC24 and ZSWIM8) were unable to be included in a single interaction network.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC) is one of the most common malignant neoplasms observed worldwide (1). Although early detection and therapeutic strategies for HNC, including radiotherapy, chemotherapy, immunotherapy and surgery, have substantially improved, the outcomes for patients with HNC remain poor, with an overall 5-year survival rate of only 50% (2,3). Therefore, it is important to find novel treatment strategies for HNC.…”
Section: Introductionmentioning
confidence: 99%
“…A biochemical interaction is validated between SOX11 and HSP90α through the co-immunoprecipitation with Western blot analysis. In addition, we have found that downregulation of HSP90α inhibits the malignant phenotypes of HNC cells and HSP90α upregulation is significantly associated with worse clinical outcome of HNC, suggesting HSP90α might serve as a potential prognostic biomarker and therapeutic target for HNC [84].…”
Section: Sox11 and Cancermentioning
confidence: 94%